Healthy shopper? Blood pressure testing in a shopping centre Pop-Up in England - Laura A. Edwards; Peter Campbell; Deanna J. Taylor; Rakhee Shah; David F. Edgar; David P. Crabb (BMC, 2019)
Abstract Background Improving detection of elevated blood pressure (BP) remains a public health need. We present results from a Pop-Up health check stationed in shopping centres in England. We hypothesise the rate of case detection is related to measurable 'unhealthiness' of the shopping centres. Methods A Pop-Up health check was sited in four and three shopping centres sampled from the top ten unhealthiest and top 15 healthiest shopping regions respectively, following a report ranking towns/cities based on their unhealthy and healthy retail outlets. On one day in each shopping centre, people were approached and consented to BP testing. Outcome measure was people flagged with BP ≥ 140/90 mmHg (cases). Results We detected 45 (22.6%) and 20 (13.1%) cases from testing 199 and 152 adults in the unhealthy and healthy locations respectively (relative risk 1.72; 95% confidence interval: 1.06 to 2.78). A measure of unhealthy retail outlets (e.g. fast-food outlets) within each shopping centre was associated with detection rate (R2 = 0.61; p = 0.04). Conclusion An association exists between cases of suspect hypertension found in a health check Pop-Up and measured 'unhealthiness' of the shopping centre site. Results hint at strategies for public testing of BP, potentially in the context of reducing health inequalities.